2020
DOI: 10.1155/2020/5701527
|View full text |Cite
|
Sign up to set email alerts
|

Cell Survival Is Regulated via SOX9/BCL2L1 Axis in HCT-116 Colorectal Cancer Cell Line

Abstract: Colorectal cancer (CRC) is one of the most frequent types of malignancies and one of the major causes of cancer-related death worldwide. Sex-determining region Y (SRY)-box 9 protein (SOX9) is a member of the SOX family of transcription factors which are involved in the regulation of differentiation and development. Recently, several reports suggest an important role of SOX9 in tumorigenesis since its overexpression correlates with tumor progression and poor outcome in several types of cancer; however, its role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…BCL2L1 is an oncogenic driver and antiapoptotic factor in CRC [ 49–50 ]. It was reported that the induction of BCL2L1 led to a reduction of apoptosis in CRC cell lines [ 51 ]. These findings indicated that these 14 intersection genes might be potent pharmacological targets of niacin against CRC and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…BCL2L1 is an oncogenic driver and antiapoptotic factor in CRC [ 49–50 ]. It was reported that the induction of BCL2L1 led to a reduction of apoptosis in CRC cell lines [ 51 ]. These findings indicated that these 14 intersection genes might be potent pharmacological targets of niacin against CRC and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…[15] In accordance with its function, large amounts of studies have explored the function of SOX9 expression in hepatocellular carcinoma, breast cancer, prostate cancer, lung cancer, esophageal cancer and colorectal cancer. [22,48–54] Moreover, a previous study found that H. pylori induces SOX9 expression in pretumorigenic gastric mouse cells. [11] Most recently, SOX9 expression also have received widespread attention in GC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Wnt/SOX9 signaling pathway affects cell proliferation, differentiation, apoptosis, invasion and migration, such as colorectal cancer and stem cells. [ 9 , 12 ] During the past few years, numerous evidence have revealed that SOX9 have oncogenic properties and upregulated expression of SOX9 was correlated with poor prognosis in patients with malignant tumors, including prostate cancer, [ 13 , 14 ] ovarian cancer, [ 15 ] breast carcinoma, [ 16 , 17 ] non-small cell lung cancer (NSCLC), [ 18 , 19 ] esophageal cancer, [ 20 , 21 ] colorectal cancer, [ 22 ] osteosarcoma [ 23 , 24 ] and glioma. [ 25 ] Growing evidence shows that SOX9 is associated with clinical TNM stage and indicates that SOX9 promotes migration, invasion [ 26 ] and the EMT process through the Wnt/β-catenin pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence analysis. Immunofluorescence was performed 48 h post-transfection as previously described (34). Briefly, cells were washed with ice-cold PBS and fixed in 4% p-formaldehyde for 10 min.…”
Section: Rna Purification and Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%